Patients with pemphigus vulgaris under pathology and on the background of prolonged use of high doses of glucocorticosteroid therapy – the possibility of influencing the glutathione system - Litvinov, V. A.; Makurina, H. I. (Journal of Education, Health and Sport, 2020)
Introduction. Pemphigus vulgaris (PV) is a life-threatening disease of the skin and mucous membranes that is associated with IgG antibodies that target several types of keratinocyte antigens and cause epidermal lysis (acantholysis) via intracellular signaling that activates apoptotic enzymes (apoptolysis). The aim of the study was to increase the effectiveness of treatment of patients with PV with the substantiation and development of modern methods of corrective therapy based on the study of indicators of changes in the balance of the thiol-disulfide system in the body of patients under pathological conditions and with prolonged use of high doses of glucocorticosteroid hormones (GCS). Materials and research methods. There were examined 30 patients with PV (4 men and 26 women), who were hospitalized in KU «Zaporizhzhya Regional Skin and Venereal Clinical Dispensary» ZOR, Zaporizhzhia. At the time of observation, most of the patients were aged 61-70 years. As a comparison group, 20 practically healthy people were examined, constituting a control group. Our studies were four-phase: before treatment; 2-3 weeks of maximum doses of glucocorticosteroids (stage I); 1.5-2 months before discharge from the hospital, when the patient was gradually reduced dose of systemic glucocorticosteroids and the selection of the optimal daily dose (stage II); after 5-6 months, when doses of hormones were minimal (2-3 tablets) in the absence of clinical manifestations of vesicles (stage III). Results. Our pathogenetic therapy by GCS significantly led to an increase in the level of reduced glutathione (GSH), so in particular after the third treatment stage it was at 1.52 ± 0.13 mkm / mg protein, exceeding the same rate of the first and second stages of GCS administration by 87.65 and 61.70%, respectively (p <0.05). The course of GCS therapy in patients with PV contributed to the fact that the level of reduced thiols increased significantly during each stage of therapy of the examined patients, in particular in the third stage of maintenance GCS therapy reduced thiols were determined at 15.64 ±1.23 mM / mg protein, exceeding this marker of the second stage by 36.95%, and the value of reduced thiols of the first stage by 83.78% (p <0.05). The value of reduced thiols of the group of patients with PV in the second stage was 11.42 ±1.08 mM / mg protein, and in the first stage – 8.51 ±0.92 mM / mg protein, the percentage difference between these therapeutic stages was determined in 34.19% (p <0.05). Prescribing systemic GCS to patients with PV for three stages led to the restoration of the balance of the thiol-disulfide system in patients, which manifested itself in the form of a decrease in markers: oxidized glutathione and oxidized thiols; and also in the form of an increase in the level of markers of restorative processes – glutathione reductase, glutathione peroxidase, reduced glutathione, reduced thiols, exerting a systemic positive effect on the course of the pathological process, which was reflected both in the normalization of laboratory parameters in patients and clinically in the form of stable remission. Conclusion. GCS therapy helps to normalize the activity of the antioxidant system of the human body under conditions of PV pathology, which prevents deprivation of the glutathione chain of the thiol-disulfide system during activation of oxidative and nitrosative stress processes and prevents the development of decompensation of the antioxidant system as a whole with the development of damage to key cells and target organs.